Geographical patterns of the incidence and mortality of colorectal cancer in mainland Portugal municipalities (2007-2011) - Roquette, Rita (2019)
Roquette, R., Painho, M., & Nunes, B. (2019). Geographical patterns of the incidence and mortality of colorectal cancer in mainland Portugal municipalities (2007-2011). BMC Cancer, 19(1), [512]. https://doi.org/10.1186/s12885-019-5719-9